Monitoring of the State of Speed and Strength Training of Highly Qualified Handball Players in The Training Process - Alisher Odilovich Abdalimov (Zien Journals, 2022)
In this paper, the issues of monitoring by applying the questionnaire method are considered. Through the sociological method of research, the monitoring of the state of the issue of speed and strength training in the practice of training sessions of highly qualified handball players was carried out. In the course of the study, nodal problems were identified, the solution of which will improve the speed and strength training of highly qualified handball players.
Keywords: Strength; qualities; muscles; means